Intestinal regulation of suppression of tumorigenicity 14 (ST14) and serine peptidase inhibitor, Kunitz type -1 (SPINT1) by transcription factor CDX2 - Danielsen, E. Thomas (Sci Rep, 2018)
The type II membrane-anchored serine protease, matriptase, encoded by suppression of tumorgenicity-14 (ST14) regulates the integrity of the intestinal epithelial barrier in concert with its inhibitor, HAI-1 encoded by serine peptidase inhibitor, Kunitz type -1 (SPINT1). The balance of the protease/inhibitor gene expression ratio is vital in preventing the oncogenic potential of matriptase. The intestinal cell lineage is regulated by a transcriptional regulatory network where the tumor suppressor, Caudal homeobox 2 (CDX2) is considered to be an intestinal master transcription factor. In this study, we show that CDX2 has a dual function in regulating both ST14 and SPINT1, gene expression in intestinal cells. We find that CDX2 is not required for the basal ST14 and SPINT1 gene expression; however changes in CDX2 expression affects the ST14/SPINT1 mRNA ratio. Exploring CDX2 ChIP-seq data from intestinal cell lines, we identified genomic CDX2-enriched enhancer elements for both ST14 and SPINT1, which regulate their corresponding gene promoter activity. We show that CDX2 displays both repressive and enhancing regulatory abilities in a cell specific manner. Together, these data reveal new insight into transcriptional mechanisms controlling the intestinal matriptase/inhibitor balance.